The Effect of Animation Video on Junior High School Student Reading Comprehension - alfiansyah bagas utama (Universitas Negeri Surabaya, 2024)
In this research entitled “The Effect of Animation Video on Junior High School Student Reading Comprehension.” the goal of this research to investigate the effect of animation videos on junior high school students’ reading comprehension of narrative text. This research was quasi-experimental design with pre-test and post-test. The participants in this study were 63 students, 32 for the experimental group and 31 for the control group of 8th grade students in junior high school. This class chose based on the teachers who provide classes with the same competence as the daily values of their students. The result of this study showed that there were significant differences between students before and after treatment. In conclusion, video animation as a learning medium for learning reading comprehension and narrative text material has a positive impact.